Overlapping Stents with Coil Sandwich for Ruptured Blood-blister Aneurysm in a Patient with Ipsilateral Persistent Primitive Trigeminal Artery: A Case Report and Review of Literature - Maeoka, Ryosuke (Asian J Neurosurg, 2019)
Ruptured blood-blister aneurysms (RBBAs) of the intracranial internal carotid artery (ICA) are associated with high morbidity and mortality. RBBA has been treated with trapping with high-flow bypass avoiding manipulation of RBBA. In case of the presence of persistent primitive trigeminal artery (PPTA), it is necessary to preserve the antegrade blood flow of PPTA because avoiding ischemic complications. Here, we present a case of RBBA concomitant with ipsilateral PPTA successfully treated with multistaged overlapping braided stents maintaining PPTA flow. A 30-year-old woman suffered from headache and was diagnosed RBBA of the intracranial ICA concomitant with ipsilateral PPTA. A reconstructive endovascular treatment using low-profile visualized intraluminal support (LVIS) stent was performed. However, it has recurred, and RBBA has finally been occluded after overlapping LVIS stents with coil sandwich that is not yet reported in the literature. We report the first case of overlapping LVIS stents with coil sandwich for RBBA.